Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Manufaktur Sektor Barang Konsumsi di BEI Periode 2017-2020 - Anisa Diah Febriani; Wikan Budi Utami; M. Gunawan Setyadi (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
This study aims to examine the effect of dividend policy, debt policy, and profitability on firm value in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. Based on the purposive sampling method, the total research sample was 112 companies with 4 years of research. The type of data used in this research is secondary data, in the form of financial statements of manufacturing companies in the consumer goods sector. Data analysis in this study used multiple linear regression using the SPSS statistical test tool. Simultaneous test results show that dividend policy, debt policy, and profitability have a significant effect on firm value. The partial test results show that the dividend policy variable has no effect on firm value. While the policy of debt and profitability affect the value of the company